Affect and Society in Precolonial Africa - de Luna, Kathryn M. (The International journal of African historical studies, 2013)
Oral traditions, recovered burial sites, words' shifting meanings, and other residue of early African life also resonate with affectivity, but all too often our narratives of the deep African past do not capture the emotional experiences of the subjects who shared stories of estranged families and jealous husbands,6 who visited gravesites carrying worn pebbles to purposefully deposit on the newly mounded earth of fresh graves,7 and who drew on familiar concepts and words to name new sources of both terror and honor.8 Our precolonial histories, which illuminate the causal power of, for example, novel technologies and political institutions in explaining historical change, might seem dry and overly instrumental to colleagues (and students) studying more recent periods or other world regions because they lack the narrative depth of human emotion.